2018
DOI: 10.1590/1678-4499.2017054
|View full text |Cite
|
Sign up to set email alerts
|

On the performance of three indices of agreement: an easy-to-use r-code for calculating the Willmott indices

Abstract: A key step for any modeling study is to compare modelproduced estimates with observed/reliable data. The original index of agreement (also known as original Willmott index) has been widely used to measure how well model-produced estimates simulate observed data. However, in its original version such index may lead the user to erroneously select a predicting model. Therefore, this study compared the sensibility of the original index of agreement with its two newer versions (modified and refined) and provided an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 18 publications
0
24
0
2
Order By: Relevance
“…(8)); Willmott's index of agreement (d) (Willmott, 1981) (Eq. (9)), which indicates how well model-produced estimates simulate observed data (Pereira et al, 2018); performance index of Camargo and Sentelhas (1997) (c) (Eq. (10)), which is the result of multiplying r and d, therefore, aggregates the information provided by both indicators, making it easier to visualize; mean error (me) (Eq.…”
Section: Validation Of Results and Statistical Analysismentioning
confidence: 99%
“…(8)); Willmott's index of agreement (d) (Willmott, 1981) (Eq. (9)), which indicates how well model-produced estimates simulate observed data (Pereira et al, 2018); performance index of Camargo and Sentelhas (1997) (c) (Eq. (10)), which is the result of multiplying r and d, therefore, aggregates the information provided by both indicators, making it easier to visualize; mean error (me) (Eq.…”
Section: Validation Of Results and Statistical Analysismentioning
confidence: 99%
“…( 4)-( 7), and refer to modelled and observed data; ̅ and ̅ are the mean values of modelled and observed data; and define the standard deviation of the modelled and observed data; and n is number of observations. In the 95 % confidence interval of each index value was calculated through bootstrap approach as contained in (Pereira et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the CRU dataset appears to be substantially better than the CPC owing its low error statistics. The proposed by Willmott et al (2012) and demonstrated by Pereira et al (2018) was used to test the level of agreement of the datasets relative to the reference observations over the study domain. The results obtained from the are similar to those from r. However, the range of values obtained using are generally lower but yet credible enough to reveal the accuracy of the datasets.…”
Section: Analysis Of Pdfs For Minimum and Maximum Temperaturesmentioning
confidence: 99%
“…In this sense, five methods were used to evaluate the residuals calculated by the cross-validation, MSE (6), R 2 (7), square root of the MSE (RMSE) and modified Willmott's concordance index (md) (8), where Z u i is the mean and Ẑ u i is the fitted value. The md index is less sensitive to the presence of outliers and has a range between 0 and 1, where values close to 1 better indicate the model's performance in the prediction [36].…”
Section: Evaluation Of the Modelsmentioning
confidence: 99%